UNIT 7.22 Selective Depletion of Abundant RNAs to Enable Transcriptome Analysis of Low‐Input and Highly Degraded Human RNA. Issue 1 (4th January 2016) - Munafó, Daniela B.; Langhorst, Bradley W.; Chater, Christine L.; Sumner, Christine J.; Rodríguez, Deyra N.; Russello, Salvatore; Gardner, Andrew F.; Slatko, Barton E.; Stewart, Fiona J.; Sinicropi, Dominick; Morlan, John; Qu, Kunbin; et al.
Abstract : Ribosomal RNAs (rRNAs) are extremely abundant, often constituting 80% to 90% of total RNA. Since rRNA sequences are often not of interest in genomic RNA sequencing experiments, rRNAs can be removed from the sample before the library preparation step, in order to prevent the majority of the library and the majority of sequencing reads from being rRNA. Removal of rRNA can be especially challenging for low quality and formalin‐fixed paraffin‐embedded (FFPE) RNA samples due to the fragmented nature of these RNA molecules. The NEBNext rRNA Depletion Kit (Human/Mouse/Rat) depletes both cytoplasmic (5 S rRNA, 5.8 S rRNA, 18 S rRNA, and 28 S rRNA) and mitochondrial rRNA (12 S rRNA and 16 S rRNA) from total RNA preparations from human, mouse, and rat samples. Due to the high similarity among mammalian rRNA sequences, it is likely that rRNA depletion can also be achieved for other mammals but has not been empirically tested. This product is compatible with both intact and degraded RNA (e.g., FFPE RNA). The resulting rRNA‐depleted RNA is suitable for RNA‐seq, random‐primed cDNA synthesis, or other downstream RNA analysis applications. Regardless of the quality or amount of input RNA, this method efficiently removes rRNA, while retaining non‐coding and other non‐poly(A) RNAs. The NEBNext rRNA Depletion Kit thus provides a more complete picture of the transcript repertoire than oligo d(T) poly(A) mRNA enrichment methods. © 2016 by John Wiley & Sons, Inc.